Answer:
x = -7 2/3, y = 1 1/3 and z = 5 1/3.
Step-by-step explanation:
2x+4y+3z=6 ..... 1
x-2y+z=-5 ...... 2
-x-3y-2z=-7 .......3
Add equations 2 and 3 to eliminate x:
-5y - z = -12 .....4
Multiply equation 2 by - 2:
-2x + 4y - 2z = 10
Add this to equation 1:
8y + z = 16 ........ 5
Now add equation 4 to equation 5:
3y = 4
y = 4/3 = 1 1/3.
Now find z by substituting for y in equation 4:
-5(4/3) - z = -12
z = 12 - 20/3
z = 36/3 - 20/3 = 16/3 = 5 1/3.
Finally, we find x by substituting for y and z in equation 1:
2x + 4*4/3 + 3*16/3 = 6
2x = 6 - 16/3 - 16
2x = 18/3 - 16/3 - 48/3 = -46/3
x = 23/3 = 7 2/3.
the two consecutive even integers are:
x
x+2
x+x+2=2
2x+2=2
2x=0
x=0
x+2=2
-12 and 18
hope this helps :)
Answer:
36=x^2+5x
x^2+5x-36=0
(x+9)(x-4)
x= 4
x= -9
The Answer can be 4 or -9, see which option you have.
Step-by-step explanation: